2020
DOI: 10.1002/cphc.202000573
|View full text |Cite
|
Sign up to set email alerts
|

Merging Gradient‐Based Methods to Improve Benchtop NMR Spectroscopy: A New Tool for Flow Reaction Optimization

Abstract: Emerging low cost, compact NMR spectrometers that can be connected in-line to a flow reactor are suited to study reaction mixtures. The main limitation of such spectrometers arises from their lower magnetic field inducing a reduced sensitivity and a weaker spectral resolution. For enhancing the spectral resolution, the merging of Pure-Shift methods recognized for line narrowing with solvent elimination schemes was implemented in the context of mixtures containing protonated solvents. One more step was achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In this regard, Morris et al have shown that PSYCHE with water suppression using excitation sculpting (ES) can be successfully applied to record 1 H pure shift spectra of ubiquitin in 90% H 2 O/10% D 2 O . Farjon et al have also combined pure shift methods and WET180 presaturation technique using a benchtop low-field NMR spectrometer to analyze simple mixtures of metabolites . To date, the problem of suppressing the water signal from pure shift spectra recorded for the purpose of metabolic profiling on a high-resolution NMR spectrometer has not been tackled yet.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Morris et al have shown that PSYCHE with water suppression using excitation sculpting (ES) can be successfully applied to record 1 H pure shift spectra of ubiquitin in 90% H 2 O/10% D 2 O . Farjon et al have also combined pure shift methods and WET180 presaturation technique using a benchtop low-field NMR spectrometer to analyze simple mixtures of metabolites . To date, the problem of suppressing the water signal from pure shift spectra recorded for the purpose of metabolic profiling on a high-resolution NMR spectrometer has not been tackled yet.…”
Section: Introductionmentioning
confidence: 99%
“… 112 The variety of nuclei, techniques, and ongoing advances also makes this method widely applicable to different chemistries, which may not be suitable for MS or chromatography. 113 For example, insights gained from mechanistic analysis can inform reaction optimization and flow NMR has been utilized for the in situ study of reactive organometallics representing catalytic intermediates. 114 Even common challenges in NMR such as overlapping peaks have been overcome utilizing state of the art algorithms.…”
Section: Data Collectionmentioning
confidence: 99%
“…Flow NMR has the advantage of having highly transferable data analysis, high information content, and moderate acquisition times (∼0.5 s scan –1 ) . The variety of nuclei, techniques, and ongoing advances also makes this method widely applicable to different chemistries, which may not be suitable for MS or chromatography . For example, insights gained from mechanistic analysis can inform reaction optimization and flow NMR has been utilized for the in situ study of reactive organometallics representing catalytic intermediates .…”
Section: Data Collectionmentioning
confidence: 99%
“…Their lower sensitivity can sometimes be offset by concentrating the samples or using a variety of methodologies for the enhancement of Boltzmann polarization [ 4 ]. Similarly, issues with chemical shift resolution can be addressed through the application of different signal acquisition and processing techniques, including solvent suppression and gradient-based pulse sequences [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%